SAVING BEHAVIOR OF THE MILLENNIAL GENERATION IN JAKARTA - Pamungkas, Ary Satria; Herwindiati, Dyah Erny; Taba, Muhammad Idrus (International Journal of Application on Economics and Business, 2025)
Indonesian people's interest in saving has decreased to only 15.4% as of May 2024. Bank Indonesia invites the public, especially the millennial generation, to get into the habit of saving. This study aims to determine the effect of peer influence, socialization of parents and self-control on saving behavior. The number of samples in this study was 240 people from the millennial generation who already have income in Jakarta. This study used Structural Equation Modelling (SEM) for data analysis. The results of this study show that peer influence, socialization of parents and self-control have a positive effect on saving behavior.